Doing involvement: A qualitative study exploring the 'work' of involvement enacted by older people and their carers during transition from hospital to home - Dr. Natasha Hardicre; Dr. Jenni Murray; Rosie Shannon; Dr. Laura Sheard; Yvonne Birks; Dr. Lesley Hughes; Dr. Alison Cracknell; Rebecca Lawton (Wiley, 2021)
Abstract Context Being involved in one's care is prioritised within UK healthcare policy to improve care quality and safety. However, research suggests that many older people struggle with this. Design We present focused ethnographic research exploring older peoples' involvement in healthcare from hospital to home. Results We propose that being involved in care is a dynamic form of labour, which we call 'involvement work' (IW). In hospital, many patients 'entrust' IW to others; indeed, when desired, maintaining control, or being actively involved, was challenging. Patient and professionals' expectations, alongside hospital processes, promoted delegation; staff frequently did IW on patients' behalf. Many people wanted to resume IW postdischarge, but struggled because they were out of practice. Discussion Preference and capacity for involvement was dynamic, fluctuating over time, according to context and resource accessibility. The challenges of resuming IW were frequently underestimated by patients and care providers, increasing dependence on others post‐discharge and negatively affecting peoples' sense and experience of (in)dependence. Conclusions A balance needs to be struck between respecting peoples' desire/capacity for non‐involvement in hospital while recognising that 'delegating' IW can be detrimental. Increasing involvement will require patient and staff roles to be reframed, though this must be done acknowledging the limits of patient desire, capability,and resources. Hospital work should be (re)organised to maximise involvement where possible and desired. Patient/Public Contribution Our Patient and Public Involvement and Engagement Panel contributed to research design, especially developing interview guides and patient‐facing documentation. Patients were key participants within the study; it is their experiences represented.